2016
DOI: 10.1016/j.rec.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Care Between Acute and Chronic Heart Failure: Critical Steps in the Design of a Multidisciplinary Care Model for the Prevention of Rehospitalization

Abstract: Despite advances in the treatment of heart failure, mortality, the number of readmissions, and their associated health care costs are very high. Heart failure care models inspired by the chronic care model, also known as heart failure programs or heart failure units, have shown clinical benefits in high-risk patients. However, while traditional heart failure units have focused on patients detected in the outpatient phase, the increasing pressure from hospital admissions is shifting the focus of interest toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 46 publications
(148 reference statements)
0
41
0
3
Order By: Relevance
“…17 We believe this to be reason enough to adapt the transition to discharge from the emergency department in an organised fashion according to the resources available in each setting, whether this be the day hospital, outpatient clinic or primary care. 24 F I G U R E 1 Flow diagram of the AHF-ID study. AHF, acute heart failure; ID, iron deficiency; TSAT, transferrin saturation…”
Section: Discussionmentioning
confidence: 99%
“…17 We believe this to be reason enough to adapt the transition to discharge from the emergency department in an organised fashion according to the resources available in each setting, whether this be the day hospital, outpatient clinic or primary care. 24 F I G U R E 1 Flow diagram of the AHF-ID study. AHF, acute heart failure; ID, iron deficiency; TSAT, transferrin saturation…”
Section: Discussionmentioning
confidence: 99%
“…Special circumstances in which NIV use could imply increased risk merit discussion. There is general agreement that failure to improve the prognosis of patients with AHF during the last decades has been due, in part, to the lack of a definition of the different scenarios and different therapeutic approaches, as well as the unclear transition strategies undertaken in a paradigmatic multidisciplinary syndrome such as AHF [22][23][24]. Therefore, the targets of therapy for AHF should not only be to improve symptoms and hemodynamics, but also to preserve or improve renal function, prevent myocardial damage, modulate neurohumoral and inflammatory activation, manage other comorbidities, identify precipitants, and avoid secondary effects of treatments in particular subgroups of patients [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Evidence indicated that transitional care components varied among the existing models, which mostly included predischarge and postdischarge elements and were delivered by a multidisciplinary team. 20,22 However, transitional care for patients with COPD remains challenging due to the complexity of disease conditions. Although a meta-analysis showed effectiveness of transitional care in reducing hospital readmission rates in subjects with COPD at Ͼ 6 and 18 months after discharge, 23 this effect was found in a meta-analysis involving only a few studies including papers published from 1999 to 2013.…”
Section: Introductionmentioning
confidence: 99%